Commodification of Islamic Hijab and Fashion Trends - Cut Munawara (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2020)
The development of the times, many aspects have changed, one of which is hijab. Now hijab is one of the fashions that is in demand by women with its simple and easy-to-use model, especially with the spread of hijab tutorials with various models, and the important thing is that hijab is a trend in this era. The purpose of this study is to describe the factors that encourage female students of Ar-Raniry State Islamic University to use hijab and the tendency of female students of Ar-Raniry State Islamic University to use commodified hijab. This research is field research using descriptive qualitative approach. To complement the results of the research the author also uses literature review. Furthermore, to collect data the author uses observation, interview and documentation methods. The data that has been obtained is analyzed descriptively and draws conclusions. The results of this study indicate that there are three factors that encourage female students of Ar-Raniry State Islamic University to use the hijab, namely because of their religious beliefs, the existence of Qanun and parental demands. Then there are also three reasons for the tendency of female students of Ar-Raniry State Islamic University to use the commodified hijab, namely the model, social class and comfort.